The Translation Problem of Equivalence on Harry Potter and the Order of the Poenix - Gita Damayanti Sinaga; Nike Anastasya Sinaga; Dian Madelina; Rajes Siregar; Anastasia Labedeva (The Explora, 2025)
The findings of this study demonstrate that achieving true equivalence in machine translation, particularly when dealing with literary texts like Harry Potter and the Order of the Phoenix, presents a range of complex challenges. Through a detailed comparison based on Mona Baker’s theory, the analysis identifies frequent issues at the lexical, grammatical, textual, and pragmatic levels. Google Translate, despite its efficiency in generating rapid translations, often fails to accurately render expressions with cultural significance, nuanced emotional tones, and figurative language. Idiomatic phrases, in particular, tend to be translated literally, stripping them of their intended meanings and stylistic impact. Grammatical inconsistencies are also observed, such as incorrect tense usage, awkward word order, and the omission of important syntactic elements, all of which compromise the clarity and naturalness of the target text.Textual cohesion and pragmatic appropriateness are similarly affected. Translated segments sometimes lack logical flow or contextual relevance, which hinders readers’ comprehension and disrupts the immersive experience that is essential to literary storytelling. The absence of cultural sensitivity in translation is especially evident in references unique to the source culture, which are either misinterpreted or rendered in ways that do not resonate with the Indonesian audience. These recurring challenges highlight the limitations of relying solely on machine translation tools for literary works, where meaning is layered and context-dependent. Although machine translation can serve as a useful preliminary tool, its outputs require extensive human intervention to ensure both linguistic accuracy and cultural fidelity. The study ultimately emphasizes the need for integrating post-editing practices into translator training programs, not only to improve translation quality but also to develop students’ analytical skills and intercultural competence in handling complex texts in the digital age.